2014
DOI: 10.4292/wjgpt.v5.i3.183
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic heart disease, factor predisposing to Barrett’s adenocarcinoma: A case control study

Abstract: AIM:To define the significance of ischemic heart disease (IHD) (stable angina to infarction) co-existance in Barrett esophagus (BE) patients and patients with esophageal adenocarcinoma (AdE). METHODS:All BE/AdE patients in Blackpool-WyreFylde area and Trikala prefecture identified from medical records. Patient clinical details were obtained from hospital and General Practitioner records. Additional information was gathered from validated questionnaire. RESULTS:Forty (33%) AdE and 83 (19%) BE patients had IHD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In Patient Summary, Jane saw that the group is associated with hypertension and diseases of oesophagus. It has been reported that there might be relationship between heart disease (e.g., ischaemic heart disease) and diseases of oesophagus (e.g., Barrett's esophagus) [78]. The group also showed high contribution scores of bilirubin, suspected as a predictive marker of pulmonary arterial hypertension [77].…”
Section: Case Study: Patients With Heart Failurementioning
confidence: 97%
“…In Patient Summary, Jane saw that the group is associated with hypertension and diseases of oesophagus. It has been reported that there might be relationship between heart disease (e.g., ischaemic heart disease) and diseases of oesophagus (e.g., Barrett's esophagus) [78]. The group also showed high contribution scores of bilirubin, suspected as a predictive marker of pulmonary arterial hypertension [77].…”
Section: Case Study: Patients With Heart Failurementioning
confidence: 97%
“…Today, data concerning BE patients with ischemic heart disease are scarce. We have reported that low-dose aspirin could reduce the risk of EAC in BE patients with ischemic heart disease, but it had no beneficial effect in patients without cardiovascular co-morbidities [53] , possibly due to cofactors common to the etiology of ischemic heart disease and EAC, such as alcohol, tobacco, diet and exercise.…”
Section: Nsaids and Eac Chemopreventionmentioning
confidence: 99%
“…Because reactive oxygen species are overproduced in the ischemic tissue [92] and various angiogenic factors are abundant in patients with cardiovascular diseases [93] , NSAIDs are expected to be more effective in this patient group. Nevertheless, non-aspirin NSAID are not effective in BE patients with ischemic heart disease, while aspirin is especially effective in this patient group [53] . Although low-dose aspirin clearly prevents EAC when prescribed in healthy controls, it suppresses COX insufficiently [34] .…”
Section: Mechanisms Of Nsaid Chemopreventive Effectmentioning
confidence: 99%
See 1 more Smart Citation